2015
DOI: 10.1093/aobpla/plw068
|View full text |Cite
|
Sign up to set email alerts
|

Trait coordination, mechanical behaviour and growth form plasticity of Amborella trichopoda under variation in canopy openness

Abstract: Finding that Amborella trichopoda is sister to the rest of the angiosperms has raised the question of whether it shares certain key functional trait characteristics and plastic responses apparently widespread within the angiosperms at large. With this in mind, Trueba et al. tested the hypothesis that local canopy openness induces plastic responses in Amborella. The authors provide evidence of intraspecific coordination between leaf and stem economic spectra in this key species. Moreover, by presenting the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 110 publications
2
10
0
Order By: Relevance
“…Previous investigations have found that plants with thicker stems and larger leaves are frequently accompanied by less frequent branching with wider branching angles (Cornelissen, 1999;Corner, 1949;Trueba et al, 2016;Wright & Westoby, 2002. Accordingly, we found larger leaves and canopies areas to be characteristic traits of the MR ecotype ( Table 3).…”
Section: Adaptive Syndrome Trait Correlations Within the Mr Ecotypesupporting
confidence: 71%
“…Previous investigations have found that plants with thicker stems and larger leaves are frequently accompanied by less frequent branching with wider branching angles (Cornelissen, 1999;Corner, 1949;Trueba et al, 2016;Wright & Westoby, 2002. Accordingly, we found larger leaves and canopies areas to be characteristic traits of the MR ecotype ( Table 3).…”
Section: Adaptive Syndrome Trait Correlations Within the Mr Ecotypesupporting
confidence: 71%
“…In the same line of thought, (Olson et al 2009) claimed that the negative trade-off between the volume of an axis and its density is a corollary to Corner’s rules and the LSR. This is in agreement with the recent work of (Trueba et al 2016) at an intraspecific level, since leaf area was shown to be a negative trade-off with both leafing intensity and stem density according to canopy openness in a New-Caledonian woody shrub species. We are first the show that this aspect of Corner’s rules applies to the leaf scale, considering lobes as counterparts of the branching process.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, this aspect of Corner’s rules applies to the leaf scale, considering lobes as counterparts of the branching process. Above all, this functional dimension (branching and leafing intensities) has rarely been studied (White, 1983a; Ackerly & Donoghue, 1998; Kleiman & Aarssen, 2007; Olson et al, 2009; Osada et al, 2015; Trueba et al, 2016) and is far from being integrated in the leaf or global spectra of economy (Westoby et al, 2002; Westoby and Wright, 2003; Wright et al, 2004; Díaz et al, 2016), whereas it is directly linked to the optimization strategy of leaf area partitioning (Smith et al, 2017) and hence light-interception performance (Duursma et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Drought tolerance was also found to be higher for C. canephora genotypes displaying smaller leaves [42]. In fact, it is known in other plants that smaller leaves allow for more rapid convective heat loss, resulting in lower transpiration and water loss likely due to smaller boundary layer [94]. Furthermore, a more compact crown structure may result in reduced VPD air within the coffee canopy, decreasing the transpiration demand [14], besides allowing to increase plant density coupled with improved soil covering and reducing the negative impacts of elevated temperatures, and high wind speed on coffee trees.…”
Section: The Impact Of Climate Changes On Coffee Crop: Warming and Wamentioning
confidence: 88%